Perbandingan Kenaikan Berat Badan pada Pasien yang Menggunakan KB suntik 1 Bulan dengan KB suntik 3 Bulan di Bidan Praktik Mandiri Wilayah Kerja Puskesmas Kragilan Serang, Banten Tahun 2023 - Dian Retha Dwiyana; Sandy Armandha Adianto Djojosugito; Susanti Susanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Weight gain can be a concern for some women, with some considering a body conforming to specific beauty standards as an ideal or desired goal. The use of progesterone hormone injections, which affect the appetite control center in the hypothalamus, can increase appetite and potentially lead to weight gain. This research employs a descriptive-analytical method with a quantitative approach conducted at the Independent Midwife Practice in the working area of the Kragilan Serang Community Health Center, Banten, using secondary data from medical records. Data collection involved 96 respondents divided into 48 samples of 1-month injectable contraceptive (KB Suntik) users and 48 samples of 3-month injectable contraceptive users. The total research sample size is 96 respondents, with the majority falling in the 20–40 age group and the remainder aged >40 years. The results indicate that among the 48 respondents using the 1-month injectable contraceptive, the average weight gain is 0. 938 kg, while for the 3-month injectable contraceptive, the average weight gain is 4. 251 kg.